Stimulasi Kemampuan Berpikir Simbolik Menggunakan Aktivitas Playdough pada Kelompok B RA Ashabul Kahfi Kota Parepare - Nurul Asqia; Ashari, Novita; Razak, Rasmida (Anakta : Jurnal Pendidikan Islam Anak Usia Dini, 2022)
The purpose of this study was to stimulate symbolic thinking skills using playdough activities in group B RA Ashabul Kahfi, Parepare City. The method used in this research is descriptive qualitative method. Data collection is done by interviews, observation and documentation. Playdought activities can stimulate the ability to think symbolically in group B which includes the ability to say the symbols for numbers 1-10, use the symbols for numbers to count, match numbers with symbols for numbers, recognize various kinds of symbols for vowels and consonants and represent various objects in the form of pictures or writing. Based on the research activities carried out, it was found that there was an increase in children's symbolic thinking skills by using playdough activities.